REVIEW OF THE PHYSICAL CONDITION OF FEMALE ROWING ATHLETES IN KUANTAN SINGINGI DISTRICT - Rati Lanosiansa; Aref Vai; Ali Mandan (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the physical condition of female rowing athletes in Kuantan Singingi Regency. This study is a study with a quantitative descriptive approach, because the data is presented in the form of numbers and analyzed based on statistical analysis. The sample in this study was 9 female rowing athletes from Kuantan Singingi Regency. The instruments in this study were physical ability tests for sports, namely sit and reach tests, abdominal muscle endurance measurements, arm muscle endurance measurements, VO2MAX measurements, power tests and measurements or explosive power tests. Data analysis will be analyzed using descriptive statistics in the form of frequency tabulation by describing the research results obtained from various test measurements of the level of physical condition. The results showed that: Abdominal and arm muscle endurance still needs improvement because abdominal muscle endurance is 44.4% in the